Potensi Pohon Lokal untuk Fitostabilisasi Logam Berat pada Tanah Tercemar Limbah Sianidasi Emas di Lombok Barat - E. Handayanto; BD Krisnayanti; N Muddarisna (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
The discharge of mercury amalgamation and cyanidation tailings of small-scale gold mining in West Lombok to agricultural lands caused Hg, Cd, Cu, Pb and Zn contamination. Phytostabilization may be a feasible approach for the management of contaminated sites. The objective of this study was to search for tree species that are potential for phytostabilization of soils contaminated by small-scale gold mine tailings in West Lombok, Indonesia. Results of this study showed that there were at least 28 tree species found in areas contaminated by gold cyanidatation tailing. Based on cyanide concentration, Hg concentration, and energy of above-ground parts of the identified plants, Duabanga moluccana (DM), Erythrina orientalis (DM)., and Paraserianthes falcataria (PF) were selected to study their phytostabilization potential. Results of plant growth experiment showed that the tolerance of the three species to heavy metals was in the order of Zn > Pb > Cu > Cd. The highest concentration of Cd (0.9 mg/kg) was found in the roots of DM. The highest concentration of Cu (37,7 mg/kg) was found in roots of EO. Roots of PF contained the highest concentrations of Pb (37.7 mg/kg) and Zn (546 mg/kg). The three plant species had metal shoot / metal root ratios of less than one. This indicates that Duabanga moluccana, Paraserianthes falcataria, and Erythrina orientalis are suitable for phytostabilization of Cu, Pb, Cd, and Zn in gold cyanidation tailing contaminated soils of West Lombok, Indonesia